ANALISIS PERSEPSI MAHASISWA AKUNTANSI TERHADAP NIAT MAHASISWA UNTUK MENGUNGKAPKAN KECURANGAN (WHISTLEBLOWING) AKADEMIK - Senara Ernawati, Rosalia; Risal; Wulandari, Renny; Mayasafitri, Rina (Jurnal Akuntansi, Auditing dan Investasi, 2023)
Accounting students as prospective accountants should behave ethically and have the courage to reveal anacademic fraud if they become aware of a fraud case that has occurred. This study aims to determine the effect ofsubjective norms, attitudes toward behavior, behavioral control and the seriousness of fraud on the intention ofaccounting students to disclose fraud (whistleblowing). This study uses a questionnaire to collect the requiredinformation. In collecting data, researchers used a sampling technique using a purposive sampling method. Thepopulation of this study was 174, the number of questionnaires collected was 110 respondents who had filled outand submitted questionnaires. The results showed that subjective norms and perceptions of behavioral controlhad no effect on students' intentions to reveal academic cheating, while perceptions about attitudes towardbehavior and the seriousness of cheating had a significant effect on students' intentions to disclose academiccheating.